THE INFLUENCE OF BRESSON’S DECISIVE MOMENT AND RODCHENKO’S CONSTRUCTIVISM ON SPORTS IMAGES - Norberto, Filipe; Morais de Oliveira, Erivam (Revista Gênero e Interdisciplinaridade, 2023)
This photo shoot aims to apply the theories learned in the Photography class of Universidade Federal de Viçosa (UFV) during the second semester of 2010. The Aleksander Rodchenko’s constructivist look was the starting point for the photographies about sports that were taken in Buritizal-SP. The photo shoot also intend to show possibilities of pictorial innovation in those instants called as decisive moments for Cartier Bresson, aiming to break the paradigm of that in the sports coverage is attempted to focus, with few exceptions, on simple plans and restricted angles in meaning.